Analyzing the effect of social support and community factors on customer engagement and its impact on loyalty behaviors toward social commerce websites. - Molinillo-Jiménez, Sebastián; Anaya-Sánchez, Rafael; Liébana Cabanillas, Francisco (My University, 2019)
While research into customer engagement receives much attention, few studies have examined why consumers engage in social commerce and the resulting consequences for companies. This study explores the influence of social support and community factors on customer engagement and the subsequent effects on customer loyalty toward social commerce websites. We propose a model to investigate the differences between the influence of social support and three community factors (community drivenness, community identification and community trust) on customer engagement, and the impact of customer engagement on four customer loyalty dimensions, one transactional (repurchase intention) and three non-transactional (willingness to co-create, stickiness intention and positive eWOM intention). We conducted a survey and collected data from 437 users of Facebook social commerce websites. The findings show that customer engagement is a key predictor of the four dimensions of customer loyalty toward social commerce websites. In addition, the results indicate that social support and two community factors significantly affect customer engagement. We discuss theoretical and managerial implications.
Keywords: Comercio electrónico; Comunidad; Consumidores - Preferencias; Social commerce; Customer engagement; Customer loyalty; Social support; Community identification; Community trust